Isolation and identification of a viral haemorrhagic septicaemia virus (VHSV) isolate from wild largemouth bass Micropterus salmoides in China - Zhang, Wanwan (Journal of fish diseases, 2019)
© 2019 John Wiley & Sons Ltd.